PENGUKURAN TINGKAT KEMATANGAN TATA KELOLA TEKNOLOGI INFORMASI PADA INSTANSI PEMERINTAHAN XYZ MENGGUNAKAN COBIT 4.1 - Purwanto, Irfan; Winarno, Wing Wahyu; Nasiri, Asro (Universitas Janabadra, 2020)
Â The use of information technology in government processes can improve efficiency, effectiveness, transparency, and accountability in government administration. At the local government agencies there are several obstacles, namely the lack of optimal supervision from the informatics section in the implementation of IT Governance, because it is done if there are complaints from other parts of the IT services and the lack of planning and alignment of the Information Technology strategy with the agency strategy. Therefore, measurement of COBIT process maturity model is needed to determine the condition of the IT process maturity model in government agencies today. The implementation of good IT governance is expected to ensure that IT investment has contributed to the progress of the institution. This research results in recommendations for improvement and improvement of information technology governance in the offices of government agencies. In this study, the conclusion of maturity level in the domain PO2 = 2.4, PO3 = 2.5, PO10 = 2.5, ME1 = 2.5 and ME4 = 2.7, so that governance at local government agencies is at level 2.5 (Defined Process).Â Â Keywords: COBIT, IT Governance, Maturity Level